SEGURANÇA DO PACIENTE NA ATENÇÃO PRIMÁRIA EM SAÚDE: SABERES E PRÁTICAS DO PROFISSIONAL ENFERMEIRO - Silva, Amarilis Pagel Floriano da (2018)
Introduction: patient safety represents an important concern in the quality of health care and has an analogy with the prevention of errors in care. Adverse events take place wherever health care is provided and, in many circumstances, could be prevented through preventive measures. Objective: to identify the actions of the professional practice of nurses that indicate patient safety in primary health care, with a view of qualifying health care. Specific Objectives: to identify, in the literature the area, the scientific publications related to patient safety actions related to the nurses' performance in primary health care and to understand the conceptions of nurses working in the Family Health Strategy on safety knowledge and practices of the patient in primary health care. Methodology: This dissertation was developed in two stages, one consisting of a integrative review of literature in which scientific articles were found with the objective of the review. The second stage consisted of a descriptive-exploratory study with a qualitative approach, developed in Family Health Strategies located in the western region of Santa Maria - RS. The data were analyzed according to the thematic content analysis of Minayo. This research is approved by the Research Ethics Committee of the Franciscan University, and is registered under opinion nº 1.876.855. Results: The publications found in the review totaled 10 scientific articles presented in a synthesis table, in order to characterize the publications according to author / year, objectives, type of study, approach, results and conclusions. In field research, the analysis process resulted in the organization of three thematic categories: Patient safety meanings for the nurses of the Family Health Strategy; Barriers to safe care in the context of Primary Health Care and Strategies for safe care in the work of nurses of the Family Health Strategy. Discussion: the findings of the integrative literature review did not allow a more in-depth analysis of the topic, since the studies about nurses' work in primary care related to the subject are scarce and incipient, indicating the existence of spaces for new research to be carried out. Many articles, because they are international, have brought a primary health care organization that is very similar to the Family Health Strategy model and traditional Basic Health Units, which are characteristic models of Primary Care in Brazil. In the field research, it was noticed that the conception of the majority of the nurses regarding the safety of the patient are related to the safe care that avoids damages. Some participants highlighted the concern about infection prevention as one of the criteria for avoiding risk and harm. Some difficulties were also signaled both in the speeches and in the professional performance, through the observations. Although many difficulties have been mentioned and observed in nurses' work, it is important to highlight that they have been developing some strategies to promote safe care, even in adverse working conditions. Final Considerations: the integrative review made it possible to identify and ponder existing studies on nurses' performance in primary care pertinent to patient safety. The data allowed to address nurses' understanding of the patient's knowledge and safety practices in primary health care, as well as the main barriers and strategies for the development of safe care. It is necessary to explore in depth questions related to patient safety in the work of nurses, since this topic presents a strategic role in the planning and implementation of health team actions and in the direct supervision of the work of Community Health Agents. attributions are heavily included actions of health promotion and care management, which impacts on a role of articulation and leadership towards the team.